Marketing Plans : How to prepare them, how to use them - McDonald, Malcolm (Amsterdam ; London : Elsevier Butterworth-Heinemann, 2007)
In this text, the process of marketing planning - from initial assessment of a company's business plan to the steps necessary to ensure a company achieves its profit targets - is fully explained.
Previous ed.: Oxford: Butterworth-Heinemann, 2002.
Includes index.
Keywords: Marketing; Marketing -- Planning; Business and Management